2016
DOI: 10.1007/s00417-016-3478-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of focal macular electroretinograms after indocyanine green-, brilliant blue G-, or triamcinolone acetonide-assisted macular hole surgery

Abstract: The lack of significant differences on the different components of the fmERGs indicates that none of the three agents was toxic to the macula. After closure of a MH, the function of the retinal ganglion cells may recover more than that of the other neural elements in the macular area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…88 However, a similar paper, reporting on 48 eyes of 48 patients with a macular hole in which, the same three agents were used (16 per agent) found no differences in focal macular electroretinogram outcomes between agents; it concluded that none of the three agents is toxic to the macula. 90 Triamcinolone acetonide has been safely used to visualize residual vitreous to facilitate removal of the ILM with good results and low concerns for toxicity. 76,80 Importantly, when the surgeon prefers ICG to stain the ILM, efforts should be made to avoid unnecessarily high concentrations of ICG or prolonged exposure.…”
Section: P189mentioning
confidence: 99%
“…88 However, a similar paper, reporting on 48 eyes of 48 patients with a macular hole in which, the same three agents were used (16 per agent) found no differences in focal macular electroretinogram outcomes between agents; it concluded that none of the three agents is toxic to the macula. 90 Triamcinolone acetonide has been safely used to visualize residual vitreous to facilitate removal of the ILM with good results and low concerns for toxicity. 76,80 Importantly, when the surgeon prefers ICG to stain the ILM, efforts should be made to avoid unnecessarily high concentrations of ICG or prolonged exposure.…”
Section: P189mentioning
confidence: 99%
“…По данным отечественной и зарубежной литературы, снижение функциональной активности нейронов сетчатки, в том числе её внутренних слоёв, объясняется наличием операционной травмы вследствие механического воздействия на сетчатку во время удаления патологических мембран [11]. В ряде других работ зарубежных коллег схожие изменения функциональной активности нейронов возникают вследствие химического воздействия искусственных красителей, контрастирующих патологические мембраны во время операции [12,13].…”
Section: таблица 2 / Tableunclassified
“…Further, one electroretinogram and histopathology study used ICG, TA, and BBG in a pig eye model and reported that the cytotoxicity of ICG is significantly higher than that of TA or BBG [ 95 ]. Another experiment found that neither BBG nor TA use had a significant effect on postoperative mfERG (multifocal electroretinogram) responses or histology in pig eye [ 95 , 103 ]. A meta-analysis further showed that there is no significant difference in the rate of hole closure following MH surgery using BBG versus other dyes, but significantly better recovery of postoperative visual function was present when BBG was used compared to ICG or other dyes [ 104 ].…”
Section: The Surgical Techniquesmentioning
confidence: 99%